KEPUASAN KERJA KARYAWAN SEBAGAI VARIABEL INTERVENING UNTUK INTERAKSI SOSIAL DAN SOCIAL SUPPORT TERHADAP KINERJA PADA PERUSAHAAN - Muhammad Dhohir; Dyah Sawitri; Martaleni Martaleni (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to examine and analyze job satisfaction as intervening social interaction and social support on performance at the Mulia Grand Manufacturing company. The research method used is quantitative. The data collection technique uses a questionnaire method. The sample used was 130 respondents, namely all employees in the production division of the converting division. The hypothesis will be tested using the SEM PLS method via WarpPLS version 7 software. The results of the research have proven that: 1). Social interaction has a positive and significant effect on performance through job satisfaction. 2).Social support has a positive and significant effect on performance through job satisfaction. 3). Job satisfaction has a positive and significant effect on performance. 4). Social interaction has a significant positive effect on job satisfaction. 5).Social support positive and significant effect on job satisfaction. 6). Social interaction has a positive and significant effect on performance. 7).Social support has a negative and insignificant effect on performance. It can be concluded that there is a significant positive influence of social interaction on performance through job satisfaction, meaning that the relationship between social interaction and performance will increase with job satisfaction. On the other hand, this research proves that there is a significant positive influence social support on performance through job satisfaction, meaning social support influence on performance with work satisfaction. This research also proves that there is a significant positive influence of job satisfaction on performance,